Taking each day as it comes: staff experiences of supporting people with Down syndrome and Alzheimer's disease in group homes. (30th April 2013) - Iacono, T.; Bigby, C.; Carling‐Jenkins, R.; Torr, J.
Abstract Background Disability staff are being increasingly required to support adults with Down syndrome who develop Alzheimer's disease. They have little understanding of the nature of care required, and may lack input from aged care and dementia services, which lack knowledge of intellectual disability. The aim of this study was to report on the experiences of disability staff in group homes supporting residents with Down syndrome and Alzheimer's disease in relation to their under understanding of what was happening to these residents, their responses to them, and how they felt about their support role. Method Disability support staff for nine adults with Down syndrome who had a diagnosis of Alzheimer's disease were interviewed twice, over intervals of 6–9 months. Interviews were transcribed and analysed for themes. Results Three key themes emerged – (i) struggling to understand change, (ii) taking each day as it comes, and (iii) he's got a disability and that's our job. Conclusions Staff had only limited understanding of how Alzheimer's disease impacted the adults with Down syndrome, their responses to changes were ad hoc, and they used strategies on a trial and error basis. They were committed to providing care, but at the risk of rejecting input and support. The need for collaboration across disability, and aged and disability care was evident to facilitate aging‐in‐place and planned care transitions.